Beliefs, Health-Seeking Practices, and Effects of Childlessness: The Experiences of Married Women - Relon, Luzviminda P. (JPAIR Multidisciplinary Research, 2018)
In a society which recognizes the significance of children, giving birth to a child completes womanhood and the family. Thus, being a mother is synonymous with being a woman. The failure, then to become a mother, constitutes not fully achieving the status of a woman. Relatively, the desire for motherhood is inevitable and almost universal. This qualitative study analyzed the beliefs, and experiences of married women focused on their childlessness, health-seeking practices, and effects. Data were gathered through in-depth interview. Results showed that childlessness typified an unanticipated condition among the childless women. Regardless of the current age, age at marriage, marital duration, educational attainment and income, the respondents disclosed that childlessness is a condition which can be treated, provided the woman is still young. Childless women with higher income would likely seek medical help. Length of marriage disclosed to have affected the childless women’s recognition of their incapability to sire. Open communication coupled with trust, love, and understanding between couples would keep the marriage intact. Findings revealed that their self-esteem, marital relationship, relationship with relatives and friends were affected by the absence of children. Almost all of the respondents expressed that the communities they are into neither, in any way, bothered with their condition nor rejected them due to their childlessness.